Manajemen Komunikasi Pemasaran Band GUU Dalam Meningkatkan Daya Saing Di Industri Kreatif - Yanti, Marwah Fitri; Rasyi Lubis, Ira Aryanti (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study analyzes how the band GUU manages marketing communication to improve their position in the local creative industry. This independent band from Bandung has a strong visual and musical identity, which requires planned communication management. Using a qualitative case study method, data was obtained through interviews, observation, and documentation. The results show that GUU's communication management was initially spontaneous, but became more integrated after they collaborated with Orange Cliff Records. The application of Integrated Marketing Communication (IMC) can be seen in the consistency of their visual identity and their use of various digital platforms, while the AIDA model is evident in their efforts to attract attention and encourage audience response through music releases and live performances. This study confirms that planned and consistent marketing communication is crucial in strengthening the competitiveness of independent bands in the creative industry.